(untitled) (Revista de Ensino em Artes, Moda e Design, 2024)
This article aims to foster reflection on the Anthropocentric Paradigm of Modern Design and the responsibility of designers and professionals in perpetuating thoughts and behaviors stemming from modern progress, particularly in the creation and production of current objects and services. Additionally, it explores how Design can contribute to future transformations by considering socioeconomic, political, and cultural aspects in alignment with the climate changes observed over recent decades. It discusses, through a bibliographic review and without exhausting the topic, and examines perspectives on addressing new representations, narratives, and practices that foster a fulfilling way of life distinct from the catastrophic and alarming forecasts for the near future, while acknowledging human interference in all forms of life on Earth. In summary, the study presents a reflection and suggests potential contributions in the field of Design, based on a qualitative and descriptive research approach, focusing on representations, narratives, practices, and projects that are integrated and oriented toward human well-being and socio-environmental responsibility.